SUPERVISI AKADEMIK ADAPTIF DI ERA KURIKULUM MERDEKA - Nancy Pransiska; Hanna Salsabila; Annisa Aulia Syahfitri; Muhammad Iqbal (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The development of educational policies in Indonesia through the implementation of the Merdeka Curriculum requires schools and teachers to conduct learning that is flexible, differentiated, contextual, and student-centered. However, various reports indicate that many teachers still struggle to understand differentiation, design authentic assessments, and develop learning modules that align with students’ needs. This situation demonstrates that curriculum transformation cannot succeed through technical instructions alone; instead, it requires continuous academic supervision that is adaptive and responsive. This study aims to describe the characteristics of adaptive academic supervision aligned with the principles of the Merdeka Curriculum, identify supporting and inhibiting factors in its implementation, and analyze its contribution to improving teacher competence and learning quality. This research employs a qualitative method using a library research approach by examining books, articles, and scientific journals related to adaptive academic supervision in the Merdeka Curriculum era. The findings show that adaptive academic supervision emphasizes collaborative guidance, reflective dialogue, coaching, and ongoing feedback that support teachers in understanding pedagogical shifts demanded by the Merdeka Curriculum. The study also identifies several obstacles, including limited supervisory competence, insufficient time allocation, and the absence of comprehensive operational guidelines. Overall, this research highlights the importance of implementing adaptive academic supervision as a bridge between curriculum policy and classroom practice and offers practical recommendations to ensure more effective, relevant, and sustainable curriculum implementation.